Epidemiological investigation of Streptococcus bovis in yaks in different regions of Tibet - Ma, H.; Zeng, J.; Zhuo, M.; Wang, D.; Yuan, Z.; Ali, S.; Mehmood, K.; Shahzad, M.; Hameed, S.; Malik, A. I. (Polish Journal of Veterinary Sciences, 2026)
Streptococcal diseases critically harm the health and productivity of animals as well as humans, and are generally considered an obstacle in the development of the breeding industry. However, there is little data on Streptococcus bovis in different seasons in different regions of Tibet. In this study, a total of 964 yak serum samples from three different cities in the Tibet Autonomous Region, comprising 326 samples from Lhasa city, 522 samples from Naqu City, and 116 samples from Xigatse city, were collected randomly. An enzyme-linked S. bovis ELISA kit (YJ233340) was used for detection. An overall seroprevalence of 1.87% was revealed in Tibet during 2021-2024, in which the seroprevalence of Lhasa city was 3.99%, followed by Naqu City (0.96%), and Xigatse City (0%). Seroprevalence was more frequent in the spring season (6.42%) and in 2024 (11.36%). The results of this study serve as a reference for the development of sustainable policies regarding the cattle raising industry and the preventive measures for S. bovis in the Tibet Autonomous Region.